Multi‐drug‐resistant tuberculosis with galaxy and cluster signs on high‐resolution computed tomography. Issue 8 (14th September 2018) - Nakamoto, Keitaro; Sasaki, Yuka; Kokuto, Hiroyuki; Okumura, Masao; Yoshiyama, Takashi; Goto, Hajime
Abstract : The galaxy sign and cluster sign were first reported in pulmonary sarcoidosis. From those reports, these two signs became known as one of the characteristic computed tomography (CT) findings of sarcoidosis. We report a patient with pulmonary tuberculosis who had these two signs. A 44‐year‐old man was referred to our hospital for general fatigue, cough, and low‐grade fever lasting about two months. Thoracic CT showed a large parenchymal nodule arising from coalescent small nodules (galaxy sign) and clusters composed of numerous small nodules (cluster sign) in the bilateral lungs. Three specimens of sputum acid‐fast smear were negative. However, we performed a bronchoscopy, and Mycobacterium tuberculosis was proven to be positive by the acid‐fast culture test of the obtained bronchoalveolar lavage fluid. Moreover, drug sensitivity testing revealed this to be a case of multi‐drug‐resistant tuberculosis. Patients with these signs must be examined carefully to differentiate tuberculosis from pulmonary sarcoidosis. Abstract : Galaxy and cluster signs are considered useful signs indicative of pulmonary sarcoidosis. However, pulmonary tuberculosis may also show these findings. We report a patient with multidrug‐resistant tuberculosis with galaxy and cluster signs requiring differentiation from sarcoidosis on high‐resolution computed tomography.